2020
DOI: 10.37358/rc.20.1.7843
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinities Studies of Nitrated Model Peptides to Monoclonal Anti-3-nitrotyrosine Antibody

Abstract: Tyrosine nitration has been shown to be an important oxidative protein modification and play a crucial role in pathophysiological conditions, associated with oxidative stress, such as atherosclerosis and neurodegenerative disease. For a better understanding of nitration mechanism, the identification and the quantification of nitration sites represents an important research goal. Due to (i) the low levels of nitration in native proteins, (ii) structural changes induced by nitration and (iii) the specificity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Zhang et al, 2007). There is no consensus motif for Tyr nitration, but several studies have shown that nTyrs are present in flexible loops and turns and in more solvent-accessible regions (Bartesaghi et al, 2007;Darie-Ion et al, 2022;Ion et al, 2020;Sacksteder et al, 2006). The presence of a nearby charged residue also favors Tyr nitration as it enables the formation of hydrogen bonds and salt bridges (Batthyány et al, 2017).…”
Section: Tyrosine Nitrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al, 2007). There is no consensus motif for Tyr nitration, but several studies have shown that nTyrs are present in flexible loops and turns and in more solvent-accessible regions (Bartesaghi et al, 2007;Darie-Ion et al, 2022;Ion et al, 2020;Sacksteder et al, 2006). The presence of a nearby charged residue also favors Tyr nitration as it enables the formation of hydrogen bonds and salt bridges (Batthyány et al, 2017).…”
Section: Tyrosine Nitrationmentioning
confidence: 99%
“…The presence of a nearby charged residue also favors Tyr nitration as it enables the formation of hydrogen bonds and salt bridges (Batthyány et al, 2017). There are contradictory reports regarding the inhibition of Tyr nitration by the nearby Cys or Met residues in vitro (Ion et al, 2020;Smallwood et al, 2003;H. Zhang et al, 2005), but in vivo nitration is not inhibited by the neighboring Cys or Met residues (Sacksteder et al, 2006).…”
Section: Tyrosine Nitrationmentioning
confidence: 99%
See 2 more Smart Citations